Perbandingan Kepuasan Mahasiswa terhadap Kinerja Pegawai Sebelum dan Sesudah Penerapan Badan Layanan Umum (BLU) - Betty Andiyarti (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: The performance-based system of Public Enterprise (BLU) demanding educational institutions is to provide service to the community as a provider of goods or services without seeking profits and in its implementation is based on the principle of efficiency and productivity. The performance of a public Enterprise already refers to the service of the public sector who apply principles (1) simplicity, (2) clarity, (3) certainty of timing, (4) accuracy, (5) security, (6) responsibilities, (7) the completeness of facilities and infrastructure, (8) ease of access, (9) comfortability, (10) discipline, courtesy, and hospitality. In educational institutions, academic performance in the field, laboratory and process of teaching and learning should be able to provide optimal service to students as users of services, in this study, the employee's performance will be discussed on the basis of 6 (six) criteria of employees’ performance indicators in terms of quality, quantity, timeliness, effectiveness, independence, commitment and work.The purpose of the research: to see the performance of the employees of the Administration section of the Lab Manager, academic and lecturer at performance learning process in providing services to students as users of services in educational institutions.Method: This research uses qualitative type of approach. In this research will provide information about two different situations, namely the experience of the past and experience at this time, so it can be known to the satisfaction of the students against the performance of the employee before and after implementation of Public Enterprise (BLU).Results: Prior to the determine of the employee's performance in BLU provides services not yet optimal, officers have not provided accurate information to students, not working in accordance with the given service time, however after the determine of the employee's performance in BLU provides services to students and employees are already increasing duties in accordance with the auth respectively.Conclusion: The implementation of public Enterprise (BLU) can improve the performance of employees in terms of service so that it can give satisfaction to the students as a user of services in educational institutions.